Integration enhancements of a solar parabolic trough system in a Chilean juice industry: Methodology and case study. (August 2021) - Crespo, Alicia; Muñoz, Iván; Platzer, Werner; Ibarra, Mercedes
Highlights: Methodology to identify the best integration scenario of solar process heat is presented. The methodology includes data gathering, performance simulation, and pinch analysis. It was applied to a case study: a parabolic trough collector into a grape juice company. Solar heat integration at process level increased the solar fraction. Abstract: A Chilean company dedicated to grape juice production used a 696 m 2 parabolic trough collector to pre-heat the feed water of a liquefied petroleum gas boiler in a temperature range of 20–90 °C. During 2017 the solar field generated 241 MWhth of heat, a low value for a concentration collector of such dimensions located in a place with high irradiation. This study presents a methodology to identify enhanced scenarios of solar heat integration into a grape juice industry and among them select the best scenario from an energetic perspective. This methodology started with data gathering of the thermal processes of the industry and the solar field (monitoring campaign and logbook of the industry) to generate the annual thermal demand. In a second step, the maximum theoretical generation potential of the solar field (1, 107 MWhth ) was obtained with simulations in TRNSYS 18. Then, a Pinch Analysis to the process streams was performed to confirm that a higher solar heat integration potential (520 MWhth ) existed. The next step consisted of identifying different scenarios to increase the solar heat integration and analyzing them with simulations in TRNSYS 18 to identify the best-case scenario. The main increase on the solar fraction was achieved for the scenario when the collector working temperature was increased up to 140 °C and when heat was integrated at process level. Furthermore, it was concluded that one of the reasons for low solar fraction was the low thermal demand during months with high solar irradiation.